Active tuberculosis cases in the community, lessons learned: Case series - R Mohankumar; G R Rajakarthika; N R Nandhinikumari; R N Sri; G Mruganayani; J M Julieanne; A S Shereen; Ariarathinam Newtonraj; Rajesh Kumar Konduru (Journal of Current Research in Scientific Medicine, 2021)
India is working hard to eliminate tuberculosis (TB) by 2025 and one of the key strategy is active case finding (ACF) of TB by house to house visit in the community. Through this ACF, which was carried out in a rural area of Pondicherry, three active cases of TB were identified. Active cases found through ACF differs from passive cases finding mainly in health care-seeking behavior and act as a source for spreading of the disease in the community and it is imperative to discuss about them. All the three cases that were detected were having diabetes and two of them were from a scheduled community area. One among them is a “newly diagnosed” case, while the other two cases belonged to “loss to follow up” and “failure of treatment” criteria. There was a lack of motivation among these patients to seek health care and adherence to treatment; and the health system also needs to gear up to tackle these active cases in the community, so that elimination of TB can be achieved by 2025. All the cases were notified with the health system and appropriate intervention was started.